ANALYSIS OF COMMUNITY CASH WAQF INTENTION TO SUPPORT SUSTAINABLE DEVELOPMENT GOALS (SDGs): THEORY PLANNED BEHAVIOUR APPROACH - Alif Khuwarazmi Maulana Julendra; Silvi Sri Mulyani; Arfi Mulyasa Insani (Universitas Airlangga, 2021)
The SDGs outline 17 goals that are part of the sustainable development agenda. One of the efforts that can be made to alleviate poverty around the world is by utilizing